Pengabdian Masyarakat: Pengembangan Model Asuhan Keperawatan Dasar Untuk Masyarakat Di Daerah Terpencil - Ferdinandus Suban Hoda (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Communities in remote areas still face limited access to health services, particularly basic nursing care. Geographical conditions, limited health resources, and low public awareness are key factors affecting the quality of health services. This community service activity aims to develop a basic nursing care model tailored to the needs of communities in remote areas through an educational and community empowerment approach. Implementation methods include identifying health needs, basic nursing education, mentoring self-care practices, and pre- and post-activity evaluations. The results of the activity indicate an increase in community knowledge and skills in performing basic nursing care independently. The development of this basic nursing care model is expected to increase community independence and become an alternative solution for improving health in remote areas.